METTL3 Promotes Activation and Inflammation of FLSs Through the NF-κB Signaling Pathway in Rheumatoid Arthritis - Shi, Wen; Zheng, Yan; Luo, Shuai; Li, Xiaofeng; Zhang, Yilong; Meng, Xiaoming; Huang, Cheng; Li, Jun (Frontiers in Medicine, 2021)
Rheumatoid arthritis (RA), a common autoimmune disease, is extremely damaging to human health. Fibroblast-like synoviocytes (FLSs) have a vital role in the occurrence and development of RA. Methyltransferase-like 3 (METTL3), which is a crucial component of the N6-methyladenosine (m6A) methyltransferase complex, is involved in the progression of many diseases. In this study, we explored the role of METTL3 in the inflammatory response and proliferation, invasion, and migration of FLSs. We used human RA synovial tissues and the adjuvant-induced arthritis (AIA) animal model of RA. Experimental results revealed that METTL3 expression was significantly upregulated in human RA synovial tissues and in the rat AIA model. METTL3 knockdown suppressed interleukin (IL)-6, matrix metalloproteinase (MMP)-3, and MMP-9 levels in human RA-FLSs and rat AIA-FLSs. In contrast, they were increased by METTL3 overexpression. Additionally, we found that, in FLSs, METTL3 may activate the nuclear factor (NF)-κB signaling pathway. The experimental results showed that METTL3 may promote FLS activation and inflammatory response via the NF-κB signaling pathway.